Influence of dynamic disturbed frequency on rock failure characteristics under triaxial cyclic and multistage unloading confining pressure loads. Issue 4 (15th January 2023) - Wang, Yu; Tang, Pufeng; Han, Jianqiang; Li, Peng
Abstract: This work aims to reveal the influence of disturbed frequency on the failure of deeply buried granodiorite under triaxial cyclic and multistage unloading confining pressure (CMSUCP) conditions. Testing results show that volumetric deformation is obviously influenced by the disturbed frequency. The volumetric strain was characterized as an early dilatancy‐dominant behavior for a sample under low disturbed frequency. The deformation development at the unloading confining pressure stage is larger than at the cyclic loading stage. The hysteresis damping decreases with increasing disturbed frequency indicating that much energy loss occurs due to damage accumulation. A first slow followed by accelerated damage propagation is expressed using a radial irreversible strain‐based damage evolution model. Macro‐meso failure pattern analysis reveals that rock dominant failure changes from mixed tensile‐shear failure to pure shear failure and a transmission from softening to hardening characteristics. It is suggested that failure develops fully for rock subjected to low disturbed frequency. Highlights: Rock triaxial cyclic and multistage unloading tests were performed. Deformation development at the unloading stage is larger than at the cyclic loading stage. A radial irreversible strain‐based damage evolution model was proposed. Macro‐meso failure reveals a dominant mixed tensile‐shear failure to pure shear failure.